MENGGENGGAM ADAT MESKI SEKEPAL TANGAN (Studi Antropologi Politik Masyarakat Adat Kaili) - , Hapri Ika Poigi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study examines three issues related to indigenous To (person) Kaili when the regional autonomy laws have no longer any influence on their culture. The three issues include how the indigenous Kaili internalizes the institutional aspects of local culture to be acted in daily life as well as emerging the social organizations? How are the position and role of traditional institutions in the perspective of indigenous peoples' past, present, and next prospects? And how the perspective of local governments, non-Government Organizations (NGOs/CBOs), and regional political elite regarding the urgency of revitalizing local culture in decentralization era? This study used a qualitative descriptive method and political anthropology to discuss. This method was considered appropriate because the most obtained research data are in the form of oral and social behavior of indigenous Kaili. Using qualitative methods, data was interpreted and formulated as it is. The research conducted in the regional indigenous To Kaili located in Palapas (Palu, Donggala, Parigi Moutong, Sigi), Central Sulawesi, has been going in a very long time. This happened because various conditions on the field made the author have to dissolve in it. The thesis was originally planned to finish within 12 months, starting in May 2006 - July 2007, but it has been achieved up to December 2010. The result of this study found that the indigenous Kaili have revitalized their cultural traditions along with the various components, such as parliament, local and central government, NGOs/NGOs, indigenous organizations, concerned individuals, humanists, sociologists and so on. They set aside their own interests and professional backgrounds to join hands together carrying out the message from their ancestors who relied in "custom is only a fist-closed, but will illuminate the world when opened". This reality is increasingly proving that the regional autonomy laws give not guarantee local culture to live worthily. The indigenous peoples should seek their own culture in order to survive, even with just the way they are. On the other hand, the state can be said to have failed to protect indigenous people (original), while the indigenous Kaili have actually been proven that they can survive without state aid.